The effect of long-distance transportation by airplane on salivary SIgA and condition in elite junior speed skaters - Kon, M.; Maegawa, T.; Suzuki, N.; Iizuka, T.; Tanisyo, K.; Yuda, J.; Aoyanagi, T.; Takaahshi, H. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Elite athletes often use airplane when they participate in an international competition. It has been reported that a longdistance transportation decreased mucosal immune function (salivary secretory immunoglobulin A: SIgA) in healthy men and women (Terasawa et al., 2008).　However, the effect of long distance transportation by airplane on salivary SIgA and condition in athlete has never been studied so far. The purpose of this study was to investigate the effect of long-distance transportation by airplane on salivary SIgA and condition in elite junior speed skaters. Methods: The subjects were 7 elite junior speed skaters who participated in the North America (Calgary) expedition in 2008. Saliva samples were collected before and after the transportation, and saliva flow rate, salivary SIgA concentration, and salivary SIgA secretion rate were measured. A survey of upper respiratory tract infection symptoms was also conducted before the transportation, 1 day, 2 days, 3days, and 4 days after the transportation. Results: The saliva flow rate (-21.4 %), SIgA concentration (-33.3 %) and SIgA secretion rate (-52.0 %) significantly decreased after the transportation (p < 0.05). One of 7 subjects exhibited upper respiratory tract infection (URTI) symptoms after the transportation. In addition, the decreasing rate of SIgA levels in the subject exhibited URTI symptoms was the highest of all the subjects. Discussion: These results suggest that the transportation decrease salivary SIgA levels in elite junior speed skaters. In addition, our data might suggest that incidence of URTI symptoms is related to the SIgA level of each subject. There is a possibility that the long-distance transportation by airplane induces a decrease in SIgA levels of elite athletes and leads to a decrease in their condition. Because saliva collection is easy and non-invasive, it is easy to enlist a cooperation of elite athletes. If it becomes possible to measure salivary SIgA more easily, the monitoring of SIgA levels may be useful for the conditioning of elite athletes with an aim to prevent the incidence of URTI during long-distance transportation.